On the origin of Piurko’s list of Romani words in the work of Miklosich - Beníšek, Michael (Romano džaniben, 2020)
The focus of the article is a dialectological analysis of a Romani wordlist that was published in 1872 by Franz Miklosich with an introductory note `A wordlist recorded in the vicinity of Uzhhorod and provided to me by Mr. Piurko’. The article discusses the linguistic material from the dialectological viewpoint and comes to the conclusion that the words cannot represent a dialect of Romani from the vicinity of Uzhhorod, but rather a dialect of the Abov (Abaúj) region spoken in and around the town of Košice (Kassa).